Strategic integration of big data in supply chain management: Unlocking innovation, sustainability, and competitiveness in the new s-curve industries - Chienwattanasook, Krisada; Wongwanich, Boontharika; Wahawisan, Tanasak; Boonyapisangkhan, Artit (Edelweiss Applied Science and Technology, 2025)
This study examines the role of big data and digital transformation in revolutionizing supply chain management (SCM) in the New S-Curve industries of the Bangkok metropolitan area. Qualitative research was conducted through in-depth interviews with 21 key informants, followed by content analysis to identify key trends and insights. The findings reveal that big data integrated with technology significantly improves SCM by enabling real-time analytics, predictive decision-making, and process optimization. This leads to higher operational efficiency and better responsiveness to the market. In addition, big data facilitates sustainability by supporting environmentally friendly practices such as energy-efficient logistics and green production. Entrepreneurs leverage big data to create innovative business models, optimize production, and develop products that meet market needs. Despite its potential, there are challenges in adopting big data for SCM, including data quality issues, high implementation costs, and regulatory hurdles. The study highlights the need for collaboration between the public and private sectors, as well as investment in technology infrastructure and workforce development to overcome these obstacles. The strategic integration of big data and digital transformation offers significant opportunities to improve the efficiency, sustainability, and competitiveness of SCM and help the industry thrive in the digital age.